Antifungal susceptibility and clinical efficacy of chlorhexidine combined with topical ophthalmic medications against Fusarium species isolated from corneal samples - Min Kang; Yuxuan Wu; Qingquan Shi; Zhiqun Wang; Yang Zhang; Kexin Chen; Xizhan Xu; Man Zhou; Qingfeng Liang; Xinxin Lu (Frontiers in Cellular and Infection Microbiology)
ObjectiveThis study investigated the susceptibility of various Fusarium fungi to five topical antifungal agents: natamycin, voriconazole, chlorhexidine, natamycin combined with chlorhexidine, and voriconazole combined with chlorhexidine. And to explore the clinical feasibility of combination therapy in the treatment of corneal infections caused by F. solani, with the goal of optimizing the treatment regimen for fungal keratitis.MethodsA total of 194 strains of Fusarium were isolated from the corneas between 2013 and 2024 and identified to the species level using mass spectrometry. The MICs was determined using a commercial microdilution plate to assess the in vitro activity of the drugs used alone and in combination (natamycin/chlorhexidine, voriconazole/chlorhexidine). Additionally, the clinical efficacy was prospectively observed in 5 patients with corneal infections caused by F. solani. The treatment regimens included 5% natamycin combined with 0.04% chlorhexidine, chlorhexidine used alone, or natamycin used alone, with follow-up lasting up to 90 days.ResultsF. solani species complex (FSSC, 46.91%) and the F. fujikuroi species complex (FFSC, 45.88%) were the predominant isolates, with a geographical distribution concentrated in Northern China. The MICs for natamycin in FSSC and FFSC were both 2–8 μg /mL, respectively. The MICs for FSSC and FFSC respectively ranged from 0.25–16 and 1–8 μg/mL for voriconazole and 2 to > 16 μg/mL and 1 to > 16 μg/mL for chlorhexidine. The MICs of natamycin were not significantly different between FSSC and FFSC. However, voriconazole, chlorhexidine, natamycin combined with chlorhexidine, and voriconazole combined with chlorhexidine had significantly higher MICs for FSSC compared with FFSC. Compared with voriconazole, voriconazole combined with chlorhexidine exhibited enhancement of antifungal activity against 100% of tested Fusarium strains. Compared with natamycin, enhancement of antifungal activity of natamycin combined with chlorhexidine was 81.4% for all Fusarium spp., and the activity were significantly lower for F. solani (65.9%) than for non-F. solani species (93.6%). Among the 5 patients, 3 patients received treatment with natamycin combined with chlorhexidine, resulting in clinical cure in 2 patients (in 1-1.5 months), while 1 patient required a corneal transplant due to delayed treatment. One patient treated with natamycin alone and one treated with chlorhexidine alone both achieved clinical cure (in 2-3 months).ConclusionNatamycin combined with chlorhexidine and voriconazole combined with chlorhexidine exhibited enhancement of antifungal activity against Fusarium spp. during in vitro sensitivity tests. The findings of this study provide valuable guidance for establishing the epidemiological cutoff and clinical MIC values for Fusarium spp. This study paves the way for future multicenter studies on the treatment of FK with natamycin and chlorhexidine.